2012
DOI: 10.2147/jmdh.s27638
|View full text |Cite
|
Sign up to set email alerts
|

Motivators, enablers, and barriers to building allied health research capacity

Abstract: PurposeA sound, scientific base of high quality research is needed to inform service planning and decision making and enable improved policy and practice. However, some areas of health practice, particularly many of the allied health areas, are generally considered to have a low evidence base. In order to successfully build research capacity in allied health, a clearer understanding is required of what assists and encourages research as well as the barriers and challenges.Participants and methodsThis study use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
295
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 161 publications
(315 citation statements)
references
References 34 publications
19
295
0
1
Order By: Relevance
“…However, it is acknowledged that engaging the clinical workforce in research has its challenges. Challenges that have been reported within radiation therapy include limited time, research facilities, access to mentors and workforce capacity 4, 5, 6…”
Section: Introductionmentioning
confidence: 99%
“…However, it is acknowledged that engaging the clinical workforce in research has its challenges. Challenges that have been reported within radiation therapy include limited time, research facilities, access to mentors and workforce capacity 4, 5, 6…”
Section: Introductionmentioning
confidence: 99%
“…This finding is consistent with other literature that delineates the paramount role that mentors have in working with clinicians to develop their research skills. [8,14,22] This relationship requires having sufficient time for for the mentors to work with the teams to develop and conduct a research project with clear deliverables, timelines, and assigned responsibilites. [15] Support for mentorship and targeted team-based education for building research capacity has been reported in other studies.…”
Section: Discussionmentioning
confidence: 99%
“…[11] However, undergraduate and postgraduate entry to practice courses may not always equip nurses and health disciplines with the competencies required to undertake research. [14] Further, despite efforts to build research capacity through a variety of initiatives (e.g. educational programs, fellowships, funding), [6][7][8][15][16][17] nurses and health care professionals continue to report lacking skills and confidence to conduct research due to minimal or no experience and not having enough time to participate in research.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations